Analysis Of China's Belt And Road Initiative (BRI) Policy In The Concept Of Balance Of Power - Nahar, Muhamad Akbar Yaumul (CV. Era Digital Nusantara, 2024)
The Belt and Road Initiative (BRI) or better known as the